Identification of a simplified mathematical model of an unmanned aerial vehicle - A. A. Lobaty; Y. F. Yatsyna; S. S. Prohorovith; Y. A. Hvitko (Системный анализ и прикладная информатика, 2020)
The problem of determining the shape and parameters of a mathematical model in the form of a transfer function for the movement of an unmanned aerial vehicle (UAV) in the vertical plane of space is solved. The angle of deviation of the Elevator is considered as the input signal, and the pitch angle of the UAV is considered as the output signal. We use the results of experimental studies of UAV flight, which are considered as known values of input and output signals under specified flight conditions. The measured discrete values of the experimental results are approximated by a fourth-order polynomial based on regression analysis for ease of use in identification. The analytical substantiation of the need to apply the methods of linearization of the mathematical model of UAV movement and the accepted assumptions for obtaining differential equations of UAV movement relative to the center of mass, allowing to synthesize the required transfer function of the corresponding element of the UAV control system. The results of computer modeling confirmed the validity of the synthesized mathematical model obtained on the basis of structural and parametric identification. This approach can be used to obtain simplified mathematical models that are used to solve problems of synthesis and optimization of control systems not only for UAVS, but also for other dynamic objects.